Time-domain Continuous-time Delta-sigma Modulator using VCO-based Integrator and GRO-based Quantizer - Lee, Eunsang; Han, Jaeduk (Journal of semiconductor technology and science, 2022)
This paper presents a 3rd-order time-domain continuous-time delta-sigma modulator (CTDSM) using two voltage-controlled oscillator (VCO)-based integrators and a gated ring oscillator (GRO)-based quantizer. The GRO-based quantizer has 1st-order noise-shaping characteristics without the increase of the signal transfer function (STF) order and has magnificent linearity. Also, the output of the GRO-based quantizer has an intrinsic data weighted averaging (DWA)-based dynamic element matching (DEM) pattern that is less susceptible to the DAC mismatch. The PWM signal, which is the input of the GRO-based quantizer, is generated by the VCO-based integrator without additional blocks. In the pre-layout simulation, the CTDSM consumes 3.84 mW and achieves an SNDR of 71.2 dB at a 400-MSs sampling frequency and a 10-MHz bandwidth. KCI Citation Count: 0